Capacity Building In Scaling Smart-Valleys Approach For Land And Water Development In Inland Valleys In Mali - Djagba, Justin; Doumbia, Salif; Konake, Sory; Dossou-Yovo, Elliott (2024)
Since the launch of the “Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA)”, numerous climate-smart agricultural technologies are being deployed at a large scale in Mali. Smart-Valleys is one of these CSA technologies. It is a farmer-led approach designed to improve water management in inland valleys while enhancing resilience to both drought and flooding. In Mali, Smart-Valleys is being scaled through the establishment of demonstration sites, capacity-building initiatives, and awareness-raising campaigns. These efforts are spearheaded by key partners of the AICCRA project, including the Africa Rice Center, the Institute for Rural Economy, the Ministry of Agriculture, and the World Bank-funded Food Security Resilience Program. In 2024, training sessions were provided to 49 trainers of trainers including four women from 12 institutions who are currently supporting over 1,000 farmers including 67% of women in the adoption of Smart-Valleys in their inland valleys.